Regional Integration in East Asia : Challenges and Opportunities, Part 1. History and Institutions - Sakakibara, Eisuke; Yamakawa, Sharon (World Bank, Washington, DC, 2014)
Over the past decade, regional integration has become the focus of intense global interest and debate, and the regionalization of East Asia has figured prominently in that dialogue. East Asia can be described as a heterogeneous region that is both global and intraregional. The authors examine the motivating factors and underlying dynamics of the progression toward closer cooperation in the region beginning from a historical perspective, which sets the stage for an evaluation of the form that regional cooperation might take so as not to sacrifice the benefits of the region's already achieved openness. This examination includes a review of the lingering effects of the 1997-98 Asian crisis, the expanding role of China in the region, the prolonged slump in Japan's economy, and the evolution of regional institutions such as the Asia-Pacific Economic cooperation and the Association of Southeast Asian Nations, among others. The authors focus on trade, direct investment, and the financial and monetary aspects of regional cooperation. In their analysis, they compare other regions, particularly the European Union and the North American Free Trade Agreement. Finally, the authors suggest cooperative steps the region might take over the next decade to promote the growth and stability of its member economies. In this regard, they look at the future role of regional institutions, the prospects for a regional role in promoting trade and foreign direct investment, and the possibilities for financial and monetary cooperation.